Novel folded pendulum residual seism accelerometer for the Virgo gravitational wave observatory: parasitic resonance mode characterisation - Džafić, Harun (Student Undergraduate Research E-journal!, 2018)
Optical components of a gravitational wave (GW) detector must both actively and passively be isolated from microseisms to be able to detect GWs. Active attenuation is achieved by making use of accelerometers within seismic isolation systems. Herein, a characterisation of the internal leg mode resonances of an improved design Folded Pendulum accelerometer, present at the Virgo GW observatory, is being discussed. We model internal leg mode resonances of the accelerometer using Finite Element Method analysis and we experimentally confirm the horizontal in-plane and tilt resonances below 1 kHz, by use of a shadow sensing application combined with Bode plots.